2005
DOI: 10.1016/j.meatsci.2005.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH on rheological properties of porcine myofibrillar protein during heat induced gelation

Abstract: Texture of meat products is dependent on the gelation characteristics of myofibrillar protein. Gaining an understanding of the gelation mechanism of meat gel systems is beneficial for the development of processed meat products as well as maintaining quality in meat products. The aim of this study was to investigate the impact of pH (5.6, 6.0, 6.5, and 7.0) on heat-induced gelation properties of myofibrillar proteins from porcine semimembranosus muscle. Dynamic rheological measurements were taken as the tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 16 publications
6
50
0
Order By: Relevance
“…The pH, ionic strength, temperature, heating rate, protein concentrations and other factors influenced the WHC (Camou, Sebranek, & Olson, 1989;Chou & Morr, 1979;Huff-Lonergan & Lonergan, 2005;Kristinsson & Hultin, 2003;Westphalen et al, 2005;Yongsawatdigul & Park, 1999). Westphalen et al (2005) found a direct linear relationship between WHC and pH, which was consistent with Offer and Trinick's findings (Offer & Trinick, 1983), and attributed the relationship to the possibility of increased protein-water hydrogen bonding at high pH values. Liu et al (2010) also found that the WHC of myosin gel decreased as the pH decreased close to the pI and proteins tended to coagulate due to increased protein-protein interactions.…”
Section: Whc Of the Heat-induced Myofibrillar Gel At 65°csupporting
confidence: 80%
“…The pH, ionic strength, temperature, heating rate, protein concentrations and other factors influenced the WHC (Camou, Sebranek, & Olson, 1989;Chou & Morr, 1979;Huff-Lonergan & Lonergan, 2005;Kristinsson & Hultin, 2003;Westphalen et al, 2005;Yongsawatdigul & Park, 1999). Westphalen et al (2005) found a direct linear relationship between WHC and pH, which was consistent with Offer and Trinick's findings (Offer & Trinick, 1983), and attributed the relationship to the possibility of increased protein-water hydrogen bonding at high pH values. Liu et al (2010) also found that the WHC of myosin gel decreased as the pH decreased close to the pI and proteins tended to coagulate due to increased protein-protein interactions.…”
Section: Whc Of the Heat-induced Myofibrillar Gel At 65°csupporting
confidence: 80%
“…Additionally, the CY at pH 5.5 was also improved with higher salt level (0.6 M). Although WHC was lowest at the isoelectric point (PI) of protein, increased salt levels improved WHC (Westphalen et al, 2005). Thus, CY at high salt level (0.6 M) improved, regardless of the pH value.…”
Section: Cooking Yield and Gel Strengthmentioning
confidence: 96%
“…The dynamic oscillatory measurements were performed using a method described by Westphalen, Briggs, and Lonergan (2005) with slight modifications on a rheometer (Anton Paar, Physica MCR 301, Austria) in oscillatory mode. A 25 mm-parallel steel plate geometry with a 500 μm gap was used.…”
Section: Dynamic Rheological Measurementsmentioning
confidence: 99%
“…G 0 in Table 3 is defined as the initial G' before heating. And the rate of gelation from 60 to 80°C is extracted from the slope of the storage modulus versus time (Westphalen et al, 2005), which is associated with the degree of protein unfolding and aggregation. In consequence, it would affect gel properties.…”
Section: Effects Of Ph On the Rheological Properties Of Mp-fg Gelmentioning
confidence: 99%